Membrane targeting peptides toward antileishmanial activity: Design, structural determination and mechanism of interaction - Martins, Danubia Batista [UNESP] (2017)
Background: Leishmaniasis threatens poor areas population worldwide, requiring new drugs less prone to resistance development. Antimicrobial peptides with antileishmanial activity are considered among fulfilling alternatives, but not much is known about the mode of action of membrane-targeting peptides, considering promastigote and infected macrophage membranes. In a previous work, structural features of very active known peptides were prospected using molecular dynamics simulations. Methods: Combining sequences of these peptides, analogs were designed. The structure of analog DecP-11 was validated by NMR. In vitro bioassays determined the peptide cytotoxicity toward mammalian cells, IC50 values on promastigotes and amastigotes, and membranolytic activity compared to Decoralin, one of the parent peptides. With biophysical methods, the mechanism of interaction with membrane mimetic systems was investigated. Results: The designed peptide exhibits potent cytolytic and membrane permeabilizing activities, and decreased antileishmanial activity compared to the parent peptide. Interactions with lipid bilayers mimicking those of promastigotes, infected macrophage and mammalian cells showed that these peptides strongly bind to vesicles with intense lytic activity at low concentrations. Additionally, circular dichroism and light scattering experiments showed changes in the secondary structure of peptides and in vesicle size, depending on vesicles compositions. Altogether they suggest that DecP-11 antileishmanial activity is impaired by the aggregation and that aminophospholipids are probably involved. Conclusions: DecP-11 potent cytolytic and membranolytic activities with lack of selectivity toward promastigote model membranes warrant further structural studies to improve selectivity.